Objective Voice Analysis of Mongolian Adults with a Normal Voice Across Age and Gender - Sodnompil, Nergui; Palamdorj, Ganchimeg; Lkhuvsandagva, Byambasuren; Lkhagvasuren, Khorolsuren; Gombojav, Bayasgalan; Zorigtbaatar, Bolortsetseg; Boldbaatar, Damdindorj (Central Asian Journal of Medical Sciences, 2021)
Objectives: We aimed to standardize main vocal parameters including fundamental frequency (F0), jitter, shimmer, harmonic-noise ratio (HNR), and smoothed cepstral peak prominence (CPPs) for Mongolian adults with a normal voice across a range of age groups and genders. Methods: A total of 360 voice recordings belonging to adults between 20 and 79 years old were analyzed. An acoustic analysis was performed using the Praat Program with a sustained vowel /a/ or /α/. A one-way analysis of variance and an unpaired t-test were used to measure differences in voice parameters for the age groups and genders. Results: The mean value of F0 was higher in women (254.4 ± 17.9 Hz) compared with men (149.6 ± 15.3 Hz). The average jitter was 0.26% ± 0.12% (W = 0.25 ± 0.13) and the shimmer was 1.95% ± 0.45% (W = 2.01% ± 0.45%). The mean value of HNR was 11.9 ± 1.33 dB (W = 12.1 ± 1.36 dB) and CPPs was 16.3 dB (W = 16.1 dB). Conclusion: The F0 and HNR significantly increased with age for men. The F0 and CPPs decreased, whereas the shimmer and HNR increased with age in women.